Development and Validation of Non-Verbal Social Skill Rating Scale for Mentally Ill (Indian Journal of Public Health Research & Development, 2021)
Aim: The aim of this study is to develop and validate the Non-verbal Social Skill Rating Scale for MentallyIll.Objectives:• To generate the scale items through focus group discussion.• To identify the appropriateness and relevance of items through subject matter expert rating.• To establish the psychometric properties of developed scale.• To develop norms for developed scale.Methodology: Formulation of 48 statements was done with focus group discussion. The statements were sentto 26 experts in the field of Occupational therapy, Psychiatrist Psychologist and Psychiatric Social Workerfor validating the items. Total of 48 items are validated by the experts. A total of 100 samples includingBipolar disorder, Schizophrenia, Depression, Anxiety, Schizoaffective disorder and acute psychosis wereselected for the field trial or main study those who were residing in psychiatric homes at Tamil Nadu.Samples were selected by using convenient sampling method. Socio demographic data sheet prepared byinvestigators were used for collecting baseline information.Conclusion: This research shows the assessment tool has good internal consistency and reliability. Theexpert validation was done and got good relevance. Hence, Non-verbal Social Skill Rating Scale forMentally Ill indicated that the scale is a reliable and valid measure of Non-verbal social skills, which is usedto identify the level of Non-verbal Social Skill of Mentally Ill.
Keywords: Non-verbal social skill, Mentally ill, Reliability and Validity, Occupational Therapy